(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines Mirzo Ulugbek’s role as a patron of science, education, literature, music, and visual art during the Timurid period. While Ulugbek is widely known as an astronomer and mathematician, his contribution to cultural and artistic life was also significant. The article analyzes the development of educational institutions, libraries, manuscript copying, painting, music, poetry, and historical writing in Samarkand during his reign. The study shows that Ulugbek’s cultural policy was based on the integration of scientific knowledge and artistic creativity. As a result, Samarkand became not only a center of astronomy and mathematics, but also an important center of literature, fine arts, translation, and intellectual communication.